The Role of Nurses in Ensuring Legal Protection of Patients in Nursing Clinics: Nursing Practice and Management Perspectives - Wahyu Eko Putro; Fajar Rinawati; Zainal Andy Saputra (Universitas STRADA Indonesia, 2025)
Background: Nurses play a very crucial role in protecting patient rights. Nurses don't just provide clinical services. They are also required to understand patient rights and the legal and ethical aspects that accompany them. Due to new regulations and a complex health system, nurses need to be equipped with legal knowledge. This is important so that they can carry out their duties professionally and protect patients effectively. Purpose: This research aims to examine the role of nurses in protecting patient rights, identify challenges faced in practice, and provide recommendations for strengthening patient legal protection through management support and legal training. Methods: A descriptive qualitative approach within the constructivist paradigm was used to explore nurses’ perceptions of their role in ensuring patients’ legal protection. Ten participants were purposively selected from three clinics in East Java. Data were collected through semi-structured interviews, transcribed verbatim, and analyzed using inductive thematic analysis to identify emerging themes. Results: This research identified three main themes: nurses’ legal protection measures, understanding of law and ethical responsibilities, and challenges in implementing these roles. These themes, derived through systematic coding and categorization, illustrate how nurses apply legal and ethical principles in daily clinical practice within the Indonesian healthcare context. Conclusion: Nurses play an important role in advocating for patient rights, but still face obstacles such as workload and lack of management support. Legal training and supporting policies are needed to strengthen the legal protection of patients in nursing clinics.